Body size, swimming speed, or thermal sensitivity? Predator-imposed selection on amphibian larvae - Gvoždík, Lumír; Smolinský, Radovan (BMC evolutionary biology, 2015)
BACKGROUND: Many animals rely on their escape performance during predator encounters. Because of its dependence on body size and temperature, escape velocity is fully characterized by three measures, absolute value, size-corrected value, and its response to temperature (thermal sensitivity). The primary target of the selection imposed by predators is poorly understood. We examined predator (dragonfly larva)-imposed selection on prey (newt larvae) body size and characteristics of escape velocity using replicated and controlled predation experiments under seminatural conditions. Specifically, because these species experience a wide range of temperatures throughout their larval phases, we predict that larvae achieving high swimming velocities across temperatures will have a selective advantage over more thermally sensitive individuals. RESULTS: Nonzero selection differentials indicated that predators selected for prey body size and both absolute and size-corrected maximum swimming velocity. Comparison of selection differentials with control confirmed selection only on body size, i.e., dragonfly larvae preferably preyed on small newt larvae. Maximum swimming velocity and its thermal sensitivity showed low group repeatability, which contributed to non-detectable selection on both characteristics of escape performance. CONCLUSIONS: In the newt-dragonfly larvae interaction, body size plays a more important role than maximum values and thermal sensitivity of swimming velocity during predator escape. This corroborates the general importance of body size in predator-prey interactions. The absence of an appropriate control in predation experiments may lead to potentially misleading conclusions about the primary target of predator-imposed selection. Insights from predation experiments contribute to our understanding of the link between performance and fitness, and further improve mechanistic models of predator-prey interactions and food web dynamics.
Keywords: ocas; Body Size; teplota; Larva; vážky; Salamandridae; Animals; Odonata; Tail; velikost těla; plavání; zvířata; Swimming; Temperature; Food Chain; potravní řetězec; larva